Chrysophyllum Albidum Accelerates Delayed Gastric Ulcer Healing in Rats Through Oxidative Stress Reversal and Proton Pump Inhibition (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Chrysophyllum albidum has been documented to exert its gastric ulcer (GU) healing activities by modulating blood inflammatory mediators, however, other probable in-vivo underlying mechanisms are still vague which this study sought to investigate.Materials and Methods: Male Wistar rats (120-130g) divided into 9 groups (n=15 for groups I-VII; n=5 for groups VIII & IX) viz: Groups I- positive control (DUnA); II and III–250 and 500mg/kg methanolic extract of C. albidum (MeCaB) bark respectively; IV, V and VI-100mg/kg fractions A, B and C respectively; VII–30mg/kg omeprazole; VIII-ulcerated untreated (baseline), IX-negative control. Chronic GU was induced experimentally and delayed using indomethacin with 14 days simultaneous drug treatment. Gastric ulcer score, mucin content, antioxidant and proton pump activities were evaluated by days 3, 7 and 14 of treatment. Data were expressed as Mean±SEM and P£0.05 was significant. Results: C. albidum and fractions treated groups significantly decreased gastric ulcer scores and lipid peroxidation compared with DUnA. Negative control, C. albidum and fraction treated groups significantly increased superoxide dismutase, catalase, glutathione levels and mucin content compared with DUnA group by days 3 and 7.  C. albidum, Negative and baseline control groups significantly decreased H+K+ATPase activities compared with DUnA by day14.Conclusion: C. albidum and its fractions facilitated the healing of gastric ulcer, probably by enhanced antioxidant levels, mucin content and decreased gastric H+K+ATPase activity.